„Wrzesień trzydziestego dziewiątego roku zdarzył mi się po raz pierwszy”. Opór oraz metafory klęski i oporu w twórczości Józefa Hena - Wyrembelski, Marcin (Załącznik Kulturoznawczy, 2022)
This article is devoted to Józef Hen’s novel entitled Resistance, part of the diptych Herod’s Theater, and to the metaphors of defeat and resistance in Józef Hen’s work. Polish prose narrating the 1939 September is dominated by a military perspective, which I refer to as a military-centric narrative. Hen’s novel, on the other hand, takes a different, civilian perspective – it tells the story of the fate and resistance of the civilians of one of Warsaw’s tenements in the Jewish district of Nowolipie against the German invaders during the siege. In the article, I discuss Resistance against the background of other books dealing with the tragedy and defeat of September ‘39, and reconstruct the fate of the novel, also mentioning its press and critical-literary echoes. In the following part, however, I focus my attention on the novel’s metaphorical echoes, for it is noticeable in Hen’s work that resistance and defeat – or, more precisely, the attempt to resist and the sense of life defeat – are mutually intertwined and constitute the attitude and determine the lives of the protagonists of his several other novels from the 1970s and 1980s, later than Resistance.